ANALISIS KONSUMSI ENERGI DAN EMISI CO2 PENGGUNAAN BUS LISTRIK DI KOTA YOGYAKARTA (STUDI KASUS BUS TRANSJOGJA) - , AZMI HUSEN R; , Rachmawan Budiarto, S.T., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesian transportation sector is the largest consumer of petroleum products and major source of greenhouse gas emissions. It happens because private transport is the most dominant transportation in Indonesian urban areas. The shifting of transport mode from private transport to mass public transport (buses) can reduce energy consumption and CO2 emissions. Electric bus is a bus which the source of energy derived from electricity to drive the electric motor. Electric bus is an environmentally friendly vehicle because its utilization can reduce the CO2 emissions. Public transport used in Yogyakarta city is Transjogja. The number of Transjogja bus is estimated 297 up to 442 in 2030. This number will consume energy 49728.79 up to 74007.15 kl diesel per day and will produce CO2 emissions 131.88 up to 196.27 ton per day. If the 25% number of Transjogja buses replaced with electric buses, the energy savings will be obtained 157.81% up to 10.71% and the reduction of CO2 emissions are 8.60% up to 13.64%. If the 50% number of Transjogja buses replaced with electric buses, the energy savings will be obtained 15.62% up to 21.42% and the reduction of CO2 emissions are 17.20% up to 27.28%. The use of electric buses in the future require a centralized charging station and bus stop charging stations to support the operation of electric buses.